1994
DOI: 10.1111/j.1600-0528.1994.tb00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and retreatment need of abutment teeth in patients with overdentures: a retrospective study

Abstract: The retreatment need was assessed in 148 patients wearing 125 overdentures in the mandible and 56 in the maxilla. The total number of abutment teeth was 512. During the evaluation period 44 abutments were extracted. The endpoints of the survival analysis after 6 yr were 89%, taking the loss of all abutments as the failure criterion for overdentures. During the clinical examination it was found that 31% of the abutments needed treatment while the retrospective part showed a mean yearly restoration need of 17.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The retrospective studies showed a larger and more heterogeneous range of survival rates, ranging from 34% to 93.85% at tooth level and from 38% to 100% at prosthesis level with a follow‐up of 5 to 20.5 years (Table 1). While in some studies reasons for abutment extractions after prosthesis delivery were not provided, other studies indicated that periodontitis was the main reason for extractions, followed by root fractures and caries (Eisenburger et al, 2000; Ericson et al, 1990; Keltjens et al, 1994; Shaw, 1984; Yoshino et al, 2020). When the reasons for prosthesis failure were reviewed, the loss of abutment teeth was the main cause in 4 studies (Eisenburger et al, 2000; Keltjens et al, 1994; Widbom et al, 2004; Yoshino et al, 2020), but other causes included incompatibility of mucosal surface (unable to undergo further repair), material failure, wear of the artificial teeth and denture base fracture.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The retrospective studies showed a larger and more heterogeneous range of survival rates, ranging from 34% to 93.85% at tooth level and from 38% to 100% at prosthesis level with a follow‐up of 5 to 20.5 years (Table 1). While in some studies reasons for abutment extractions after prosthesis delivery were not provided, other studies indicated that periodontitis was the main reason for extractions, followed by root fractures and caries (Eisenburger et al, 2000; Ericson et al, 1990; Keltjens et al, 1994; Shaw, 1984; Yoshino et al, 2020). When the reasons for prosthesis failure were reviewed, the loss of abutment teeth was the main cause in 4 studies (Eisenburger et al, 2000; Keltjens et al, 1994; Widbom et al, 2004; Yoshino et al, 2020), but other causes included incompatibility of mucosal surface (unable to undergo further repair), material failure, wear of the artificial teeth and denture base fracture.…”
Section: Resultsmentioning
confidence: 99%
“…A significant correlation between abutment and prosthesis survival and the number of initial abutments was reported by three retrospective studies (Eisenburger et al, 2000; Rinke et al, 2019; Yoshino et al, 2020). It was also suggested that mandibular incisors may be the least suitable teeth as abutments, since they are the ones that most frequently fail and require extractions over time (Eisenburger et al, 2000; Keltjens et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many patients, however, were reluctant to come so often because they had no evident problems and were not used to visiting the dentist regularly. Other studies have the same disappointing results, especially in the absence of a strict maintenance protocol.1 [26][27][28] The results regarding the Dyna magnetic attachments were disappointing; most were lost or in a bad condition. "Wear" of the magnet cover often occurred, which lead to cracks and the loss of magnets.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating the existing longitudinal studies of RSOs there are only 11 published articles, [30][31][32][33][34][35][36][37][38][39][40] none of which solely investigated patients with overdentures supported by two mandibular canines opposed by a complete denture. A secondary analysis of the data presented by Ettinger and Qian 40 assessed only data derived from patients that had two mandibular canines-supported overdentures opposed by a complete denture.…”
Section: Survival Rates Of Abutmentsmentioning
confidence: 99%